‘And Now I’m Teaching in a Catholic School’ – The Experiences of Early Career Teachers (ECT) in Lismore Catholic Schools and What Can Be Learned to Support Their Formation: A Preliminary Study - Challinor, Kurt; Lancaster, Joan; Rymarz, Richard (Paedagogia Christiana, 2023)
This study is a preliminary investigation of early career teachers (ECT) working in Catholic schools in a large regional Australian diocese. The key aim of the study is to better understand the factors influencing early career teachers, who begin their teaching careers in Catholic schools, and to apprehend their early experiences as teachers to cater for their continuous formation needs. Key findings identify the openness of ECTs to faith-based experiences and the challenges faced in teaching in a Catholic school. Recommendations for early career teacher support and formation are provided considering the findings of this study